PELAKSANAAN PERKAWINAN MELALUI WALI HAKIM DI KANTOR URUSAN AGAMA KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Gita Putri Candra; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The position and authority of the guardian in marriage is an important to do. As we known, he is entitled to be trustee of marriage for the bride. If there are no guardian nasab to married her then she should married by guardian judge.The conclusion that can be obtained from this research are, the most factors happened that caused guardian judge become a trustee of the bride when implementation of the marriage in Religious Affair Office Marpoyan Damai Pekanbaru City starting from 2013-2015 because there are no more guardian nasab, the guardian nasab living so far away from the bride, and disharmony relationship between them. The process of the implementation of marriage through the jugde guardian is same as general marriage.Keywoards : Implementation – Marriage - Guardian Judgje